Validation of the career adaptability scale - Tak, Jinkook; Lee, Eunjoo; Lim, Green (Korean Journal of Industrial and Organizational Psychology, 2015)
The purpose of this study was to test validity of the Korean version of the Career Adaptability Scale(CAAS) developed by Savickas(2012) based on two samples of employees. In the study 1, data were collected from 300 employees across a wide variety of companies. The total of 24 items of the Korean version of the CAAS were administered. The results of factor analyses showed that the four-factor model with 16 items was appropriate. In the study 2, data were collected from 184 employees across various companies. The results of confirmatory factor analyses showed that the four-factor model had high goodness-of-fit indices supporting construct validity of the Korean version of the CAAS. Also the results of correlation analyses showed that career adaptability was significantly related to various criteria such as perception of future career success, career planning, career satisfaction, and career commitment, confirming criterion-related validity of the Korean version of the CAAS. Finally, implications, limitations, and future studies were discussed.